The extension of collective agreements as a way to promote collective bargaining - Urdarević Bojan P. (Institute of Comparative Law, Belgrade, 2021)
Collective bargaining is a process of joint decision-making in which the social partners, representing the interests of their membership, try, in good faith, to determine the content and conclude the collective agreement. In this sense, collective bargaining is a way to resolve many issues related to the work process, to the satisfaction of all parties. In a context in which labour markets are characterized by inequality and uncertainty, the extension of the collective agreement is a key public policy instrument for the promotion of collective bargaining in general. However, certain principles must be represented to allow as many workers as possible to be covered by the extended effect of the collective agreement. These principles are set out in Collective Agreements Recommendation no. 91 of International Labour Organization and need to be followed to ensure respect for the free and voluntary nature of collective bargaining. With the fourth industrial revolution, the world of work changed radically, but the institute of the extended effect of the collective agreement can offer some answers to new circumstances, such as the increase of flexible forms of work and employment, migrant workers, or posted workers.